A Influência do planejamento mestre da produção na implementação da manufatura enxuta: o nivelamento da produção (heijunka) - Elias, Sérgio José Barbosa (2011)
This thesis approaches the influence of the master production schedule in the implementation of lean manufacturing. The Master Production Schedule (MPS) - to the lean manufacturing - needs to be leveled with the demand (heijunka), so that clients’ needs are met, without keeping the stocks high, which according to lean approach mean a loss by overproduction. In addition, the productive system needs to meet the client’s demands without overload or idleness of the productive resources. In line with that, this thesis proposes a model to diagnose the MPS, from indexes of practices adopted and the performances obtained by the organizations, in order to relate the results from those indexes to the stage of production leveling. The literature review has identified the state of the art related to the subject of this thesis, besides substantiating its newness and relevance. It is presented the proposed method - MPSBM (Master Production Schedule Benchmarking) - which enables the diagnosis of the way how the organizations operate their master production schedule, in order to obtain the leveling, besides identifying which actions might be taken, so that the heijunka happens. It aims, in this way, to highlight the relation between the MPS leveling and the lean manufacturing stage in which the productive system encounters itself, since that relation has been depicted in the theoretical discussions present in literature, without, however, owning an instrument that allows the evaluation of that relation. In order to make possible the discussion of the relations between the leveled MPS and the lean manufacturing, it has been also applied the Lean Benchmarking diagnosis (BME), which has been developed by the Laboratório de Simulação de Sistemas de Produção (LSSP), from Universidade Federal de Santa Catarina. This simultaneous analysis is based on the observation that the production leveling influences on obtaining the lean manufacturing. It is a qualitative research of exploratory and descriptive nature. To test the proposed model, it has been used in six companies, and in one of them it has been applied in three different processes, which results in eight applications. The results of the applications have provided the identification of strengths and opportunities for improvement in the production management and have enabled verifying the relationship between the leveled MPS and the stage in which the companies encounter themselves in terms of lean manufacturing, making it, in this way, an element which deserves the attention of organizations which aim a lean manufacturing.